First step on the road - Hampson, Karen J.; Perkins, Kevin (Technical Centre for Agricultural and Rural Cooperation, 2019)
Farm Radio International was invited by FAO to contribute content to an online course on experience capitalization, and later by CTA to attend the Inception Meeting of its project. Recognising the value of this approach - for improving relationships, for detailing gaps or successes, and for supporting innovation and learning - we decided to introduce it to some of our larger projects